Impact of Choppies Enterprise in Southern Africa: An Exploratory Study on Strategic Management Perspective - Simon, Taelo; Nayeem, Abdur Rakib; Alam, Md. Khorshed; Raja, Md. Shahab Ali (American Economic & Social Review, 2020)
Organizations nowadays are increasingly impacting in using strategic management to improve their performance; this study has mainly focused on the impact of strategic management on the performance of Choppies Enterprises. Choppies Enterprise Botswana-based Choppies is an investment holding company operating in the retail sector across sub-Saharan Africa. Its operations are food and general merchandise retailing as well as financial services transactions supported by centralized distribution channels, through distribution centers and logistical support assets in Botswana, South Africa, Zimbabwe, Kenya, and Zambia. This study focused on the strategic management of Choppies Enterprises. The main research problem was to make an in-depth analysis of its competitive strategy and how to implement it. The main research method was qualitative research by analyzing their company data, annual reports, and making interviews with the manager, staff, and customers in Botswana shops. The result shows a clear image of the process of strategic management by Choppies' case. Some recommendations made for Choppies help to improve their sustainable developments and support a vivid example for many companies. In the theoretical part, it described the definition, process, benefit, and challenge of strategic management. In the practical part, an exhaustive analysis of the company's strengths, weaknesses, opportunities, and threats was made by using the detailed figures.